Gold Passport: The attractiveness of Hyatt frequent guest program / Nabila Farhana Razalle - Razalle, Nabila Farhana (Faculty of Business Management, Universiti Teknologi MARA, 2011)
Hyatt Regency Kinabalu is one of the pioneer five-star hotels to be built in Kota Kinabalu, Sabah. However, as Kota Kinabalu becoming one of the emerging tourism spot, many hotelier and entrepreneurs saw this as a big opportunity. They start to build their own hotel to cater the rapidly increasing number of travelers who came to Kota Kinabalu. Not forgetting the already existed well known hotels that are viewed as major competitors by Hyatt Regency Kinabalu. These competitors include Sharing-La Tanjung Aru Resort and Spa, Le-Meridian, Sutera Harbour and Nexus Karambunai. With the intense competition, hoteliers nowadays try to find some solution to differentiate their product and services from the others and it seems that Loyalty Program is the key to do so. But the fact is majority of loyalty programs nowadays have l,ost their unique selling proposition due to the cliche "point's accumulations" and discounts. Despite the increased prevalence of loyalty programs, questions remain over their effectiveness and their role is greatly misunderstood. Do such programs create loyalty? Does the return on such initiatives justify the expenses? Or is this just another discounting that companies are forced into due to the competitive pressure? In this research, it was found that Gold Passport is not well known by the local public as it was well known by frequent travelers. There are many reasons that may lead to this issue and Hyatt Regency Kinabalu must find their way to improve their loyalty program.